ANALISIS ANALISIS DAMPAK COVID-19 TERHADAP KINERJA KEUANGAN PADA PERUSAHAAN SUB SEKTOR HOTEL RESTORAN DAN PARIWISATA YANG TERDAFTAR DI BURSA EFEK INDONESIA - Sasmito Widi Nugroho; La Ode Abdullah; Vaisal Amir (MANAJEMEN, 2021)
This study aims to determine whether there is a significant difference in company performance due to the COVID-19 pandemic (a case study on a Hotel Restaurant and Tourism Sub-Sector Company Listed on the Indonesia Stock Exchange. This research data was taken before and after the announcement of the first case of COVID-19 in Indonesia). The method used in this study is to compare financial ratios in the form of liquidity ratios, solvency ratios, activity ratios of hotels, restaurants and tourism sub-sector companies listed on the IDX before and after the national announcement of the first case of Covid-19. This study shows the results that after the Covid -19 pandemic in Indonesia, the hospitality and restaurant sub-sector companies generally experienced losses. This affects the company's ROA level, where all tourism, restaurant and hotel sub-sector companies in 2019 and 2020 are below 5.98%. This means that the company cannot take advantage of existing assets to make a profit. This is partly due to restrictions imposed by the government which make the company's sales decline.